2018
DOI: 10.1111/cns.12869
|View full text |Cite
|
Sign up to set email alerts
|

Next‐generation sequencing improves treatment efficacy and reduces hospitalization in children with drug‐resistant epilepsy

Abstract: These results offer further proof that NGS approaches represent powerful tools for establishing a definitive diagnosis. Moreover, this study indicated how NGS can improve treatment efficacy and reduce hospitalization in children with DRE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 40 publications
1
40
1
1
Order By: Relevance
“…Evidence in support of precision therapy in epilepsy varies in level and nature. In 2019, the majority of truly medically ‘actionable’ genetic diagnoses in epilepsy relate to inherited disorders of metabolism such as Glut1 deficiency, and pyridoxine dependency ( Peng et al , 2019 ). Questions remain unanswered in relation to targeted treatment of other genetic causes of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence in support of precision therapy in epilepsy varies in level and nature. In 2019, the majority of truly medically ‘actionable’ genetic diagnoses in epilepsy relate to inherited disorders of metabolism such as Glut1 deficiency, and pyridoxine dependency ( Peng et al , 2019 ). Questions remain unanswered in relation to targeted treatment of other genetic causes of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberous sclerosis Cell growth mTOR inhibitors and vigabatrin AD 0.3-3.1% 40,41,46,49,[51][52][53] Abbreviations: AR, autosomal recessive; AD, autosomal dominant; XLD, X-linked dominant; XLR, X-linked recessive.…”
Section: Tsc2mentioning
confidence: 99%
“…Genetic Characteristics In Drug-resistant Epilepsy Of Published Studies Table 3 provides a summary of previous studies about genetic characteristics in DRE [12][13][14][15][16][17][18][19][20][21]. Regardless of varied molecular diagnostic tool used between studies, some gene mutations were found to appear repeatedly, such as SCN1A (5.6%, n = 74/1308), followed by SCN8A (1.37%, n = 18/1308), TSC2 (1.22%, n = 16/1308), SCN2A (1.07%, n = 14/1308) and KCNQ2 (0.99%, n = 13/1308) 3).…”
Section: Discussionmentioning
confidence: 99%